Identification of the geochemical processes in groundwater by factor analysis in hard rock aquifers of Madurai District, South India - Thivya, C.; Chidambaram, S.; Thilagavathi, R.; Prasanna, Mohan Viswanathan; Singaraja, C.; Nepolian, M.; Sundararajan, M. (Springer, 2014)
A study was carried out in the Madurai district of Tamil Nadu, India to identify the hydrogeochemical processes using factor analysis as a predictive tool. It also focuses on characterizing the samples of these factors with respect to standard geochemical plots. In order to obtain a synoptic view of the statistics and the geochemical processes, a total of 53 groundwater samples are collected representing the entire district. The major ions were analyzed; the order of ion dominance are Ca2+ > Na+ > Mg2+ > K+ = Cl− > HCO− 3 > H4SiO− 4 > NO− 3 > SO2− 4 > P3− 4. The samples are classified according to three factors. Factor 1 shows strong positive loadings of Cl−, Ca2+, Mg2+, and NO− 3 with 36.98 % of the total variance (TV); factor 2 accounts for 13.72 % of TV with high loadings of Na+, K+, and HCO− 3; and factor 3 shows strong positive loadings of PO3− 4 and SO2− 4 with TV of 13.1 %. In the Piper plot, few samples fall in the mix region as evidenced by the mixing proportion of two samples using AQUACHEM software. The results suggest that different hydrogeochemical processes, like weathering, ion exchange processes, and anthropogenic activities (like sewage infiltration and agriculture), has predominant impact in the study area. Thus, the study highlights the factor analysis technique as a predictive and effective tool for groundwater evolution.